Respuesta :

Answer:

The standard form of y = 3 x + 1 is         -3x + y = 1 .

The standard form of y  = 4x - 7 is         -4x + y = -7.

Step-by-step explanation:

Here the given equation are:

y = 3 x + 1

and y  = 4x - 7

The above equations are of the form:  y = m x + C

Now, the STANDARD FORM of the equation is Ax + By  = C

Consider equation 1:

y = 3 x + 1

or, y - 3x  = 1

or. -3x + y = 1

⇒ The equation  -3x + y = 1  is in STANDARD FORM.

Consider equation 2:

y = 4 x - 7

or, y - 4x  = -7

or. -4x + y = -7

⇒ The equation -4x + y = -7 is in STANDARD FORM.